2007
DOI: 10.3201/eid1306.061182
|View full text |Cite
|
Sign up to set email alerts
|

Minority-Variant pfcrt K76T Mutations and Chloroquine Resistance, Malawi

Abstract: Genotyping of the chloroquine-resistance biomarker pfcrt (Plasmodium falciparum chloroquine resistance transporter gene) suggests that, in the absence of chloroquine pressure, Plasmodium falciparum parasites in Malawi have reverted to chloroquine sensitivity. However, malaria infections in Africa are commonly polyclonal, and standard PCRs cannot detect minority genotypes if present in <20% of the parasites in an individual host. We have developed a multiple site-specifi c heteroduplex tracking assay (MSS-HTA) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
61
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(63 citation statements)
references
References 16 publications
2
61
0
Order By: Relevance
“…However, in the past several years, it has been suggested that the amount of previous reports of diversity have described only the "tip of the iceberg" (10,11,16). Here we expose the extent of in-host diversity by using MPP to quantify and identify rare variants in polyclonal malaria infections in a high-throughput manner.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in the past several years, it has been suggested that the amount of previous reports of diversity have described only the "tip of the iceberg" (10,11,16). Here we expose the extent of in-host diversity by using MPP to quantify and identify rare variants in polyclonal malaria infections in a high-throughput manner.…”
Section: Discussionmentioning
confidence: 99%
“…However, nPCR with gel electrophoresis detects only size polymorphisms and cannot detect sequence polymorphisms. Furthermore, it has been shown that nPCR methods are insensitive to low-abundance variants (3,16). Last, the method is not quantitative for relative population sizes of different variants.…”
mentioning
confidence: 99%
“…Mixed infections arise from inoculations of genetically diverse parasites by a single mosquito or contemporaneous bites by multiple mosquitoes infected with different parasites. Consequently, the coexistence of drug-sensitive and drug-resistant parasites is common, and indeed may even be the rule (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22).…”
Section: Aims Of Patient Treatmentmentioning
confidence: 99%
“…8 The heteroduplex tracking assay (HTA) is a genotyping technique that has proven adept at uncovering minority variants within malaria infections and in infections with other agents. [13][14][15][16] Thus, it provides a more accurate picture of within-host genetic diversity. 17 It also facilitates the tracking of clones within hosts over time, potentially providing a nuanced portrait of relapsing vivax populations.…”
Section: Introductionmentioning
confidence: 99%